LEAD REACTIONS IN SOME CALCAREOUS SOILS OF NORTHERN IRAQ - mohammed alijamal; ali AL-Obadi (Mesopotamia Journal of Agriculture)
The adsorption experiment of three different calcareous soils (loam and clay) for Nineveh governorate (Tel Aakoub, Ibrahim Al-Khalil, and Taqlif) was classified under Aridsol-Calciorthids with a slight slant to alkaline (7.43), non saline (3.24 dS m-1), Low content of organic matter (17.3 gkg-1), cation exchange capacity (42 Cmolc kg-1), high content of carbonate minerals (409 g kg-1). Lead adsorption was studied by batch equilibrium method at a temperature of (298 Kelvin) for lead solutions (5,10,20,40,80,100 mg L-1). For 48 hours,the lead was measured in equilibrium solutions and the adsorption criteria were calculated according to Langmuir ,Freundlich and the DR equations. The results of the mathematical description of lead adsorption showed high efficiency in the use of Langmuir , Freundlich and the DR equations at the concentrations used. The lead added to the soil was also distributed between the equilibrium solution and the solid soil phase in terms of propagation coefficient values (Kd), which ranged from (111.8) to(255.5 l kg-1)with an average of 169 l kg-1. The DR equation exceeded the Langmuir and Freundlich equivalents in the description of lead adsorption to obtain the highest coefficient of determination (R2) and a lesser standard error (SE).The adsorption capacity (qm) of the lead ion in the study of soil was( 13.63 - 41.48 mol g-1).The K value associated with the adsorption capacity ranged from (-0.44) to (- 1.24) (mol2 KJ -2). The value of (E) is the free energy rate of the reaction ranged from the lead adsorption values (0.63 - 1.06 KJmol-1)